2021
DOI: 10.1002/jmv.27013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genotype distribution of high‐risk HPV infection among women in Beijing, China

Abstract: Cervical cancer (CC) is highly associated with high‐risk human papillomavirus (HPV) infection and genotype distribution of high‐risk HPV (HR‐HPV) infection varies greatly in different regions. Clinical specimens were collected from 46 365 patients at Beijing Friendship Hospital, Capital Medical University from January 2017 to December 2020. HPV DNA genotype testing was performed using real‐time PCR. The infection rates based on disease group were compared using the χ 2 test. The linear‐by‐linear association te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 37 publications
7
26
3
Order By: Relevance
“…Overall, HR-HPV prevalence in the study population at baseline was 14.4%, which was lower than 18.0%, as concluded by pooled analysis by Zhao et al from 17 population-based studies in rural China in 2010 25. In our study, the prevalence of HPV slightly declined in middle ages (40–49 years), yet increased among the oldest people (60–64 years), which are consistent with other studies in China26 27 or in some Latin America/Caribbean populations 28. A meta-analysis of 1 million women from five continents showed that age-specific HPV distribution presented with a first peak at younger ages (<25 years) and, in the Americas and Africa, a rebound at older ages (≥45 years) 29.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, HR-HPV prevalence in the study population at baseline was 14.4%, which was lower than 18.0%, as concluded by pooled analysis by Zhao et al from 17 population-based studies in rural China in 2010 25. In our study, the prevalence of HPV slightly declined in middle ages (40–49 years), yet increased among the oldest people (60–64 years), which are consistent with other studies in China26 27 or in some Latin America/Caribbean populations 28. A meta-analysis of 1 million women from five continents showed that age-specific HPV distribution presented with a first peak at younger ages (<25 years) and, in the Americas and Africa, a rebound at older ages (≥45 years) 29.…”
Section: Discussionsupporting
confidence: 90%
“…Among the participants in this study, the overall HPV positive rate including HR-HPV and LR-HPV was 15.13%, which was consistent with the study demonstrated the overall prevalence of HPV infection in China (15.54%) [16].Some results from other cities of China also reported the similar HPV prevalence [17,18,19,20,21]. However, the HPV prevalence reported was higher than Shannan (8.16%) [22] and Xinjiang (9.34%) [23] but was lower than Zhejiang Province (22.3%) [24], Beijing (22.7%) [25], Jiangxi Province (22.49%) [26] and Heilongjiang Province (27.1%) [27]. The variability of HPV prevalence may be accounted to diverse geographical condition and economy developmental level.…”
Section: Discussionsupporting
confidence: 85%
“…The high‐risk group includes HPV 16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 68, 73, and 82, infection with these types may potentially progress into invasive cervical cancer 11 . The overall prevalence of HPV infection worldwide is estimated to be nearly 10% (<3%–26%) 12 . In patients with cervical cancer the prevalence of high‐risk HPV DNA is more than 95% 13 .…”
Section: Introductionmentioning
confidence: 99%
“…11 The overall prevalence of HPV infection worldwide is estimated to be nearly 10% (<3%-26%). 12 In patients with cervical cancer the prevalence of high-risk HPV DNA is more than 95%. 13 Thus, the detection of high-risk HPV (HR-HPV) has become increasingly attractive as a primary screening tool for cervical cancer due to its sensitivity and cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%